Efficacy of traditional Chinese exercise (Baduanjin) on patients with stable COPD: A systematic review and meta-analysis - Zhihao Shuai; Qionghua Xiao; Yutong Ling; Yong Zhang; Yanxia Zhang (Complementary Therapies in Medicine, 2023)
Background: COPD is a prevalent and intractable chronic airway disease. At present, COPD is one of the diseases with the highest morbidity and mortality in the world; and causes a significant economic burden to patients and society. As a traditional exercise, the Baduanjin exercise has been inherited in China for hundreds of years. However, the treatment effects of Baduanjin exercise are controversial. This systematic review was designed to evaluate the efficacy of Baduanjin exercise in patients with stable chronic obstructive pulmonary disease. Methods: Published articles were searched in nine English and Chinese databases from inception to December, 2022. Two investigators conducted study selection and data extraction independently. Review Manager software 5.4 were implemented for data synthesis and analysis. Quality assessment for each study was based on the modified PEDro scale. Results: This review included 41 studies with 3835 participants with stable COPD. Compared with the control group, the pooled data of Baduanjin exercise group showed significant improvements in the following outcomes (mean difference, 95 % confidence interval): FVC (0.29, 0.25–0.33), FEV1 (0.27, 0.22–0.33), FEV1% (5.38, 4.38–6.39), FEV1/FVC (5.16, 4.48–5.84), 6MWD (38.57, 35.63–41.51), CAT (−2.30, −2.89 to −1.70), mMRC (−0.57, −0.66 to −0.48), SGRQ (−8.80, −12.75 to −4.86), HAMA (−7.39, −8.77 to −6.01), HAMD (−7.80, −9.24 to −6.37), SF-36 (8.63, 6.31–10.95). Conclusions: Baduanjin exercise may have the potential to enhance lung function, exercise capacity, health status, mental status, and quality of life for patients with stable COPD. Ethic and dissemination: This study is a systematic review and it does not involve harming the rights of participants. Ethical approval will not be required for this study. The research results may be published in a peer-reviewed journal.